An index system constructed for ecological stress assessment of the coastal zone: A case study of Shandong, China. (15th February 2019) - Yu, Lu; Wu, Xiaoqing; Zheng, Xilai; Zheng, Tianyuan; Xin, Jia; Walther, Marc
Abstract: Coastal zones, which have high ecological value and environmental function and play a key role in human development, face intense ecological stress from human activities. This study constructed an assessment index system for coastal zones and proposed a coastal ecological stress index (CESI) model. This method was then applied to the Shandong coastal zone. The results showed an increase in ecological stress from 2001 to 2016 and implied a further growth trend. The stress caused by terrigenous pollution was the most prominent, with the ecological stress index showing significant spatial difference. Qingdao exerted the highest ecological stress on the population and economy, while Yantai showed the highest stress on the coastal index. The CESI model effectively reflects the temporal and spatial characteristics of the coastal ecological stress and provides a theoretical basis for the management of different regions. Highlights: We proposed an index system and the coastal ecological stress index (CESI) model. Combining GIS yielded more intuitive and scientific results. The CESI of the Shandong was increased and revealed significant spatial difference. The CESI model is useful for management and decision on the coastal ecosystem.